Systémový postup havarijního plánování - Skupová, Dagmar (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Bakalářská práce se zabývá systémovým postupem havarijního plánování. Podrobně studuje vnitřní a vnější havarijní plány. Zabývá se také vhodnými metodami analýzy rizika průmyslových havárií. Součástí práce je návrh nejvhodnější metody analýzy rizika. Praktická část popisujeme moji práci s vyhodnocovacím programem zvaným ALOHA.

Bachelor thesis deals with the system progress of emergency planning. Bachelor thesis studies internal emergency plans and external emergency plans. It is engaged in suitable methods of risk analysis. One of parts of my bachelor thesis is proposal of the most suitable method of risk analysis. The practical part describes my work with assessment programme named ALOHA.
The System Progress in Emergency Planning
Keywords: havarijní plánování; krizové řízení; analýza rizika; priorizace rizika; průmyslová havárie; analýza disponibilních zdrojů; emergency planning; crisis management; risk analyse; priorization of risk; industrial accident; analyse of the available resources